Application of the New Classification on Patients with a Disorder of Sex Development in Indonesia - A. Zulfa Juniarto; Yvonne G. van der Zwan; Ardy Santosa; Remko Hersmus; Frank H. de Jong; Renske Olmer; Hennie T. Bruggenwirth; Axel P. N. Themmen; Katja P. Wolffenbuttel; Leendert H. J. Looijenga; Sultana M. H. Faradz; Stenvert L. S. Drop (International Journal of Endocrinology)
Disorder of sex development (DSD) patients in Indonesia most often do not receive a proper diagnostic evaluation and treatment. This study intended to categorize 88 Indonesian patients in accordance with the new consensus DSD algorithm. Diagnostic evaluation including clinical, hormonal, genetic, imaging, surgical, and histological parameters was performed. Fifty-three patients were raised as males, and 34 as females. Of 22 patients with 46, XX DSD, 15 had congenital adrenal hyperplasia, while in one patient, an ovarian Leydig cell tumor was found. In all 58 46, XY DSD patients, 29 were suspected of a disorder of androgen action (12 with an androgen receptor mutation), and in 9, gonadal dysgenesis was found and, in 20, severe hypospadias e.c.i. Implementation of the current consensus statement in a resource-poor environment is very difficult. The aim of the diagnostic workup in developing countries should be to end up with an evidence-based diagnosis. This is essential to improve treatment and thereby to improve the patients' quality of life.